2023
DOI: 10.22331/q-2023-03-16-947
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Correlations in the Minimal Scenario

Abstract: In the minimal scenario of quantum correlations, two parties can choose from two observables with two possible outcomes each. Probabilities are specified by four marginals and four correlations. The resulting four-dimensional convex body of correlations, denoted Q, is fundamental for quantum information theory. We review and systematize what is known about Q, and add many details, visualizations, and complete proofs. In particular, we provide a detailed description of the boundary, which consists of three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…This was observed numerically in [85]. Moreover, its bounds were analytically found to correspond to the boundaries of an elliptope, discussed in detail in [88]. 21 More formally, we establish convexity by showing that if a triple of overlaps (∆ 12 , ∆ 13 , ∆ 23 ) is pure-state realizable, then so is any triple in the line segment connecting it to (0, 0, 0), i.e.…”
Section: Theorem 10 a Triple Of Overlaps Is Realizable By Three Quant...mentioning
confidence: 64%
See 2 more Smart Citations
“…This was observed numerically in [85]. Moreover, its bounds were analytically found to correspond to the boundaries of an elliptope, discussed in detail in [88]. 21 More formally, we establish convexity by showing that if a triple of overlaps (∆ 12 , ∆ 13 , ∆ 23 ) is pure-state realizable, then so is any triple in the line segment connecting it to (0, 0, 0), i.e.…”
Section: Theorem 10 a Triple Of Overlaps Is Realizable By Three Quant...mentioning
confidence: 64%
“…This set was shown numerically to be convex in [85]. It is sometimes referred to as the body of quantum correlations, and parts of it correspond to the elliptope of [88]. In [85,88] it was shown that points in Q • 3 satisfy the inequality…”
Section: Definition 3 (Set Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…If, for instance, we want to simulate the correlation array for a Hardy-Unruh setup in Figure 9 or Figure 11 with one of our raffles, the problem is not to obtain a non-zero probability for one particular outcome, but to obtain it while at the same time obtaining zero probabilities for several other outcomes. 13 In other words, rather than focusing on individual entries, we need to consider a correlation array as a whole. 14 Despite being taken down a notch, Hardy-Unruh chains remain valuable.…”
Section: Discussionmentioning
confidence: 99%
“…The extra minus sign affects Table 1, Figure 7 and Equations ( 13) and ( 14) below. 5 See Goh et al [11], Chen et al [12] and Le et al [13] for interesting recent work in this tradition, to which Tsirelson made important early contributions (see, for instance, [14], p. 3, Figure 2). In a paper from 1987 [15], Tsirelson already noted: "As one can easily see, the set Cor(m, n) of all quantum realized m×n correlation matrices .…”
mentioning
confidence: 99%